APLIKASI MEDIA AUDIO-VISUAL DALAM PEMBELAJARAN SPEAKING SKILL DENGAN PENDEKATAN AUDIOLINGUAL:: Studi Kasus di MAN Batang - Slamet Untung (JURNAL PENELITIAN, 2011)
The research to study the application of audio and visual medium in order to learn speaking skill by audiolingual approach is a good contribution to educational world of senior high school and the Islamic one, particularly, in finding a way to improving the learning component relating directly to the medium and method of learning speaking skill. This research is to find out its significance and relevance. The main variable of this research includes the whole activities of the application of audio and visual medium in learning speaking skill by audio-lingual approach. The data were collected through observation, interview, questionnaire and documentation. This research took place in state Islamic senior high school of Batang in Central Java. The result shows that the application helps the students to speak English correctly and accurately and stresses the message of the speaking skill learning.